Theranostic of orthotopic gliomas by core-shell structured nanoplatforms - Luís D. Carlos (Light: Science & Applications, 2022)
Abstract Smart designed core-shell nanostructures formed by a YVO4: Nd3+ nanoparticle as the core, the sonosensitizer hematoporphyrinmonomethyl ether as the carrier, and MnO2 nanosheets as the shell demonstrate bimodal imaging and highly efficient sonodynamic therapy of orthotopic gliomas.